EVALUASI PENYEDIAAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PERUSAHAAN JASA KONSTRUKSI - Mekar Ria Pangaribuan (MAJALAH TEKNIK SIMES, 2018)
SMK3 dan K3 are all activities to ensure and protect the safety and helath of the workforce throught prevention of occupational injuries and occupational diseases in construction works. Research objectives: 1) Knowing SMK3 in the sampling company, 2) Obtain the effect of K3 applied. The research method used a model showing the realitionship betwen perception and preferance with attitudes by Martin A. Fishbein. The result of research indicated that the attitude of the respondent abaut the OSH sistem is the condition of the working environment is the first indicator (1,62 / 42%), the use of personal protective equipment is the second indicator (1,536 / 39%), the provision of the third director of keetutan (0,725 / 19%), and heavy equipment inspection is the lowest indicator (0,00 / 0%).